Aritmética com Python - Cavalcante, Rogério da Silva (2018)
We aim to show how effective the technological resources can be when used for teaching. We chose to use the Python programming language in mathematics teaching, specifically arithmetic, showing how logic moves naturally between computing and mathematics, thereby showing a natural interdisciplinarity between these subjects. We propose programs built from the demonstrations of some classic results of arithmetic, aiming to integrate the teaching of these results to the teaching of basic tools of a programming language.